The Influence of Social Media Tourism Campaigns and Influencer Partnerships in Building Brand Equity of Destinations in East Java - Tita Rosalina; Rella Dwi Respati; Raden Asri Kartini (Westscience Press, 2025)
This study examines the impact of social media tourism campaigns and influencer partnerships on building destination brand equity in East Java. Using a quantitative research design, data were collected from 70 respondents through a structured questionnaire with items measured on a five-point Likert scale. Statistical analysis, conducted with SPSS version 25, revealed that both social media campaigns and influencer partnerships significantly and positively influence destination brand equity, with 68% of the variance explained by these variables. The findings highlight the synergistic effect of these strategies in enhancing brand awareness, perceived quality, and loyalty. Practical implications suggest integrating these approaches for effective tourism marketing.